Economic effects of exchange-rate changes - Riechel, Klaus-Walter. (Lexington, Mass. : Lexington Books, 1978)
The author has applied the tenets of the monetary approach to the balance of payments, which is essentially a long run analysis, to scrutinize the effects of exchange rate changes in a short run context. He develops the model, considering money first as a producers good, then as a consumers good. Initially money is the only available asset, but the analysis is subsequently expanded to include non trade able domestic bonds and foreign bonds. Also he introduces non traded goods to the analysis, to permit relative price adjustment.
Includes index.
Bibliography: p. 143-150.
usc 25/05/18; 19/10/18
Loans
Keywords: Foreign exchange rates; Balance of payments; Foreign exchange